Effect of Planting Pattern on Radiation Use Efficiency, Yield and Yield Components of Sunflower - Gholipouri, Mohammad Sedghi, Beytollah Vahedi, Abdolghayoum (Recent Research in Science and Technology, 2010)
In order to determinate suitable planting pattern of sunflower, a field experiment was done in research field of university of Mohaghegh Ardabili in 2009. Factorial experiment was done based on randomized completely block design with three replication and two factor includes cultivars with three levels (Armavirusky, Azargol and Progress) and planting pattern with three levels (75*16.5, 60*20.5 and 45*27.5) with constant density (8 plant.m-2). Results of study showed that planting pattern effect was significant on head diameter and radiation use efficiency but have no significantly effect on yield and yield components. Cultivar effect was significant on yield and yield components but has no significantly on head diameter and radiation use efficiency. Among the cultivars studied, the highest grain yield (3616 kg.ha-1) belonging to Azargol cultivar and lowest grain yield (3131 kg.ha-1) belong to Progress cultivar. Therefore, it is better that according to exist facilities and machinery suitable planting pattern shall be selected and in the study area Azargol cultivar being planted.